The Role of rDNA Clusters in Global Epigenetic Gene Regulation - Tchurikov, Nickolai A.; Kravatsky, Yuri V. (Frontiers in Genetics, 2021)
The regulation of gene expression has been studied for decades, but the underlying mechanisms are still not fully understood. As well as local and distant regulation, there are specific mechanisms of regulation during development and physiological modulation of gene activity in differentiated cells. Current research strongly supports a role for the 3D chromosomal structure in the regulation of gene expression. However, it is not known whether the genome structure reflects the formation of active or repressed chromosomal domains or if these structures play a primary role in the regulation of gene expression. During early development, heterochromatinization of ribosomal DNA (rDNA) is coupled with silencing or activation of the expression of different sets of genes. Although the mechanisms behind this type of regulation are not known, rDNA clusters shape frequent inter-chromosomal contacts with a large group of genes controlling development. This review aims to shed light on the involvement of clusters of ribosomal genes in the global regulation of gene expression. We also discuss the possible role of RNA-mediated and phase-separation mechanisms in the global regulation of gene expression by nucleoli.